2014
DOI: 10.1166/jnn.2014.9213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Functionalized Magnetic Iron Oxide Nanoparticles in the Central Nervous System Injury and Repair: New Potentials for Neuroprotection with Cerebrolysin Therapy

Abstract: Functionalized Magnetic Iron Oxide Nanoparticles (FMIONPs) are being explored for the development of various biomedical applications, e.g., cancer chemotherapy and/or several other radiological or diagnostic purposes. However, the effects of these NPs per se on the central nervous system (CNS) injury or repair are not well known. This review deals with different aspects of FMIONPs in relation to brain function based on the current literature as well as our own investigation in animal models of CNS injuries. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Cerebrolysin, a neuronal metabolic activator including various free amino acids and low molecular weight peptides, has been used to treat cerebrovascular diseases for many years. Previous studies have shown that it can improve neurological outcome by preventing cell death, free radical formation and inflammation, and by counteracting excitotoxicity and accelerating the recovery of neurological function (6)(7)(8)(9). Clinical trials have shown that the usage of Cerebrolysin is reliable and effective with regard to the recovery of consciousness, language and hemiplegia in patients with AIS (11)(12)(13).…”
Section: Nbp Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebrolysin, a neuronal metabolic activator including various free amino acids and low molecular weight peptides, has been used to treat cerebrovascular diseases for many years. Previous studies have shown that it can improve neurological outcome by preventing cell death, free radical formation and inflammation, and by counteracting excitotoxicity and accelerating the recovery of neurological function (6)(7)(8)(9). Clinical trials have shown that the usage of Cerebrolysin is reliable and effective with regard to the recovery of consciousness, language and hemiplegia in patients with AIS (11)(12)(13).…”
Section: Nbp Groupmentioning
confidence: 99%
“…Cerebrolysin is a peptide-containing preparation that also exerts beneficial effects on ischemic stroke; preclinical studies have shown that Cerebrolysin substantially improves neurological outcome and promotes neurological functional recovery following ischemia by preventing cell death, the formation of free radicals, inflammation and by counteracting excitotoxicity (6)(7)(8)(9). Clinical trials have been performed to test the efficacy and safety of NBP and Cerebrolysin in the treatment of patients with acute ischemic stroke (AIS), and encouraging results have been reported (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a broad range of nanoparticles with different sizes, architectures, and surface properties have been engineered for brain drug delivery. 27,28 These include liposomes, 29,30 polymeric nanoparticles, 31,32 carbon nanotubes, 33,34 nanofibers, 35,36 dendrimers, 37,38 micelles, 39 inorganic nanoparticles made of iron oxide, 40 and gold nanoparticles. 41 Unfortunately, it is beyond the scope of this article to review potential advantages -or disadvantages -of each of these nanocarriers in the imaging and/or therapy of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…How is cerebrolysin able to reduce brain edema formation and/or BBB breakdown in TBI? This is not well known from our investigation [23][24][25][26]. However, available evidences suggests that cerebrolysin could induce neuroprotection or neurorepair because of exogenous supply of selective neurotrophic factors, e.g., brain-derived neurotrophic factor (BDNF), glial-derived neurotrophic factor (GDNF), nerve growth factor (NGF), and insulin-like growth factor 1 (IGF-1) along with many active peptide fragments needed for nutrition of neurons and glial cells [23][24][25][26].…”
Section: Discussionmentioning
confidence: 83%
“…30 min, 1 h, and 2 h after TBI. The animals were allowed to survive 8 h after injury [23][24][25][26].…”
Section: Cerebrolysin Administrationmentioning
confidence: 99%